2018
DOI: 10.3390/rs10091480
|View full text |Cite
|
Sign up to set email alerts
|

Wind Direction Inversion from Narrow-Beam HF Radar Backscatter Signals in Low and High Wind Conditions at Different Radar Frequencies

Abstract: Land-based, high-frequency (HF) surface wave radar has the unique capability of monitoring coastal surface parameters, such as current, waves, and wind, up to 200 km off the coast. The Doppler spectrum of the backscattered radar signal is characterized by two strong peaks that are caused by the Bragg-resonant scattering from the ocean surface. The wavelength of Bragg resonant waves is exactly half the radio wavelength (grazing incidence), and these waves are located at the higher frequency part of the wave spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 24 publications
5
30
0
Order By: Relevance
“…When the radar operates at higher frequencies, the resonant Bragg waves have a shorter wavelength being more sensitive to changes in the wind field. Therefore, for wind direction measurements from HFr backscatter signals, a radar with a higher operating frequency leads to estimations that are in better agreement with in situ measurements [21]. Another important factor is wind speed.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…When the radar operates at higher frequencies, the resonant Bragg waves have a shorter wavelength being more sensitive to changes in the wind field. Therefore, for wind direction measurements from HFr backscatter signals, a radar with a higher operating frequency leads to estimations that are in better agreement with in situ measurements [21]. Another important factor is wind speed.…”
Section: Introductionmentioning
confidence: 92%
“…In the literature, experiments on the validation of HFr wind direction have been generally carried out in wide coastal areas and over the ocean for periods from days to months [20][21][22][23][24][25][26]. The results show that several factors contribute to the accuracy of HFr wind measurements, the operational frequency being the most relevant one.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], Shen and Gurgel presented a pattern-fitting based method for estimating wind direction from narrow-beam HF radar Doppler spectra and further investigated the factors that affect the measurement accuracy. By employing the data collected by two radars of different frequencies (12 MHz and 27.68 MHz) under varying wind conditions, the authors showed the proposed wind direction algorithm outperformed the least-squares minimum method.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…High-frequency (HF) radar has been successfully deployed to detect ocean surface moving target and remote sensing of ocean surface dynamics such as wind direction and speed, current and wave parameters in many countries for decades [1][2][3][4][5][6][7][8][9][10][11][12][13] because it can provide real-time, all-weather surveillance beyond the horizon. Based on the geometry, HF radar can be generally divided into monostatic (transmitter and receiver are collocated) and bistatic (transmitter and receiver are separated) types.…”
Section: Introductionmentioning
confidence: 99%